2017
DOI: 10.1080/03043797.2017.1289500
|View full text |Cite
|
Sign up to set email alerts
|

Formative assessment in mathematics for engineering students

Abstract: In this paper, we present a range of formative assessment types for engineering mathematics, including in-class exercises, homework, mock examination questions, table quizzes, presentations, critical analyses of statistical papers, peerto-peer teaching, online assessments and electronic voting systems. We provide practical tips for the implementation of such assessments, with a particular focus on time or resource constraints and large class sizes, as well as effective methods of feedback. In addition, we cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 56 publications
2
12
0
Order By: Relevance
“…In addition, the homogeneous groups showed that there was no significant difference between the DCU and the MCU regarding these aspects. The superior autonomous learning of the students, and their greater knowledge of the basic concepts when following these courses, led the teachers to adopt significantly different attitudes compared to the BCU, a common situation also remarked upon in another study [ 65 ]. It may therefore be affirmed that the type of subject matter had no influence over the students’ perception of the controllable aspects of the experiment.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…In addition, the homogeneous groups showed that there was no significant difference between the DCU and the MCU regarding these aspects. The superior autonomous learning of the students, and their greater knowledge of the basic concepts when following these courses, led the teachers to adopt significantly different attitudes compared to the BCU, a common situation also remarked upon in another study [ 65 ]. It may therefore be affirmed that the type of subject matter had no influence over the students’ perception of the controllable aspects of the experiment.…”
Section: Resultsmentioning
confidence: 81%
“…As explained in Section 3.1.1 , the students of BCU are younger (around 2 years younger on BCU on average than on DCU and MCU) and at the start of their university career, when their knowledge base is weaker [ 62 ]. It implies that they tend to need closer monitoring, as they have less capacity for autonomous learning, which makes the valuation of this aspect lower than in more advanced courses [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors acknowledge that it has always been a challenge for those who teach in the mathematics discipline to provide engaging and valuable learning experiences that equally serve the needs of both mathematics and non-mathematics-focused courses. As evidenced by recent studies of higher education mathematics subjects in the United Kingdom and Europe (Fhloinn & Carr, 2017;Frode, 2017;Iannone & Simpson, 2015), subject engagement in the mathematics discipline by students is heavily influenced by whether or not a student is undertaking a course that is mathematics-focused, for example, engineering, science or actuarial studies. In fact, a closer look revealed that students who engaged with the intricacies of the mathematical method (how to arrive at a solution or answer a question) were also those who were enrolled in a mathematics-focused course.…”
Section: The Problem and Contextmentioning
confidence: 99%
“…In recent years, there has been a proliferation of educational technologies aimed at supporting the implementation of formative assessment in mathematics learning and teaching in more efficient ways. Three recent studies, completed by Barana and Marchisio (2016), Fhloinn and Carr (2017), and Frode (2017), explored automated formative assessment in mathematics in higher education in Europe. These studies provide insight into the advantages of developing automated formative assessments.…”
Section: The Problem and Contextmentioning
confidence: 99%